(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2010)
This article aims to demonstrate the importance of functional behavior analysis in behavioral evaluations and therapy involving children. A client took part who was eight years and six months old, female and with two years of schooling. Her mother sought assistance with the behavioral descriptions of her daughter: listless, agitated, aggressive, disobedient and with learning difficulties. The evaluation was conducted in six functional situations: therapistclient, therapistmother, therapistfather, therapistboth parents, therapistaunt and therapistteacher. The main procedures involved the observation of the behavioral repertoire of the client, verbal account and the application of specific tools. The functional analysis of behavior was promoted based on the formulation of hypotheses of the effects of environmental changes on the client’s complaintbehavior. Procedures of verbal and generalized reinforcement were used to increase selfesteem and develop a behavior that included better arithmetical and academic performance. Both goals were achieved. This case study demonstrated that functional analysis can be based on processes of evaluation and child psychotherapy, making them more effective.